Mutation in NPPA causes atrial fibrillation by activating inflammation and cardiac fibrosis in a knock‐in rat model. Issue 8 (29th April 2019) - Cheng, Chen; Liu, Huixia; Tan, Chengcheng; Tong, Doudou; Zhao, Yongxuan; Liu, Xia; Si, Wenxia; Wang, Liniin; Liang, Lina; Li, Jia; Wang, Chenghui; Chen, Qiuyun; et al.
ABSTRACT: Atrial fibrillation (AF) affects >30 million individuals worldwide. However, no genetic mutation from human patients with AF has been linked to inflammation. Here, we show that AF‐associated human variant p.Ile138Thr in natriuretic peptide A ( NPPA ) encoding the atrial natriuretic peptide (ANP) causes inflammation, fibroblast activation, atrial fibrosis, and AF in knock‐in (KI) rats. Variant p.Ile138Thr inhibits the interaction between ANP and its receptor natriuretic peptide receptor A and reduces intracellular cGMP levels. RNA sequencing and follow‐up analyses showed that mutant ANP (mANP) activates multiple innate immunity pathways, including TNF‐α, NF‐κB, and IL‐1β signaling. mANP induces differentiation of cardiac fibroblasts (CFs) to myofibroblasts and promotes CF proliferation and fibrosis. These results suggest that NPPA variant p.Ile138Thr causes AF by activating TNF‐α, NF‐κB, and IL‐1β signaling, inflammation, and fibrosis. Multiple computational programs suggest that p.Ile138Thr is damaging or deleterious. Based on the 2015 American College of Medical Genetics and Genomics Standards and Guidelines, p.Ile138Thr can be classified as a likely pathogenic variant. Variant p.Ile138Thr was found only in Asian people in the Genome Aggregation Database and Exome Aggregation Consortium database at an averaged frequency of 0.026%. An estimated 1.15 million Asian people carry the variant and might be at risk of AF. The KI rats may provide an inflammation‐based, genetic animal model for AF valuable for testing anti‐inflammation or other therapies for AF.—Cheng, C., Liu, H., Tan, C., Tong, D., Zhao, Y., Liu, X., Si, W., Wang, L., Liang, L., Li, J., Wang, C., Chen, Q., Du, Y., Wang, Q. K., Ren, X. Mutation in NPPA causes atrial fibrillation by activating inflammation and cardiac fibrosis in a knock‐in rat model. FASEB J. 33, 8878–8891 (2019). www.fasebj.org